2021
DOI: 10.1186/s12889-020-10055-2
|View full text |Cite
|
Sign up to set email alerts
|

Tuberculosis-related stigma and its determinants in Dalian, Northeast China: a cross-sectional study

Abstract: Background The stigma of tuberculosis (TB) poses a significant challenge to TB control because it leads to delayed diagnosis and non-adherence. However, few studies on TB-related stigma have been completed in China. The aim of the current study was to explore the status of TB-related stigma and its associated predictive factors among TB patients in Dalian, Northeast China. Methods An institution-based, cross-sectional survey was conducted among out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
43
2
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(53 citation statements)
references
References 44 publications
4
43
2
4
Order By: Relevance
“…Patients with adequate social support from family, friends and community are likely to have better QOL 20 . Furthermore, social support was also an important predictor of stigma 21 . Patients with poor social support are more likely to be isolated and alienated, with manifestations such as being denied shared utensils and food by family members and losing their jobs, which may lead to stigma 22 , 23 .…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Patients with adequate social support from family, friends and community are likely to have better QOL 20 . Furthermore, social support was also an important predictor of stigma 21 . Patients with poor social support are more likely to be isolated and alienated, with manifestations such as being denied shared utensils and food by family members and losing their jobs, which may lead to stigma 22 , 23 .…”
Section: Introductionmentioning
confidence: 98%
“…Moreover, studies have reported that TB-associated stigma is associated with psychological stress disorders. These factors can increase the risk of mental health problems, such as psychological distress 21 , 32 , 33 .…”
Section: Introductionmentioning
confidence: 99%
“…This is similar to what's reported in other parts of the world. For instance, in a study conducted in China, a high rate of stigma among TB patients was observed, particularly among females ( 11 ). Similarly, in Peru, where TB is a high burdened disease, there is a considerable lack of knowledge among participants on the symptoms; this further emphasizes the need for health literacy and education awareness ( 12 ).…”
Section: Introductionmentioning
confidence: 99%
“…More accurate and credible data from rural areas might provide glimpses of actual prevalence and current burden of disease in the country. Besides estimation of the actual burden of disease, it is imperative to raise awareness about symptoms, its mode of transmission, prevention, diagnosis and treatment, and most importantly, destigmatization of the disease through health education at the grass root level [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%